2020
DOI: 10.5483/bmbrep.2020.53.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Cardiac Mesenchymal Stromal Cells and Their Extracellular Vesicles Comparing With Human Bone Marrow Derived Mesenchymal Stem Cells

Abstract: Cardiac regeneration with adult stem-cell (ASC) therapy is a promising field to address advanced cardiovascular diseases. In addition, extracellular vesicles (EVs) from ASCs have been implicated in acting as paracrine factors to improve cardiac functions in ASC therapy. In our work, we isolated human cardiac mesenchymal stromal cells (h-CMSCs) by means of three-dimensional organ culture (3D culture) during ex vivo expansion of cardiac tissue, to compare the functional efficacy with human bone-marrow derived me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Kang I. S. et al performed a characterization of the EVs isolated from human cardiac mesenchymal stromal cells and compared them with those isolated from human bone marrow-derived mesenchymal stem cells. The in vitro results of this study demonstrated that EVs derived from human cardiac mesenchymal stromal cells exhibited a potent angiogenic effect compared to EVs derived from bone marrow mesenchymal stem cells [ 74 ]. Moreover, Leitolis A. demonstrated that EVs isolated from the human heart induced proliferation and angiogenesis in endothelial cells, promoting wound healing, and reducing the adhesion of mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kang I. S. et al performed a characterization of the EVs isolated from human cardiac mesenchymal stromal cells and compared them with those isolated from human bone marrow-derived mesenchymal stem cells. The in vitro results of this study demonstrated that EVs derived from human cardiac mesenchymal stromal cells exhibited a potent angiogenic effect compared to EVs derived from bone marrow mesenchymal stem cells [ 74 ]. Moreover, Leitolis A. demonstrated that EVs isolated from the human heart induced proliferation and angiogenesis in endothelial cells, promoting wound healing, and reducing the adhesion of mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…ADMSC-derived EVs enhanced angiogenic tube formation in human brain microvessel endothelial cells via increased expression of miR-181b-5p, which, in turn, directly targeted expression of the ion channel protein TRPM7 (Yang et al, 2018). Similarly, BMMSC-derived EVs induced angiogenic tube formation in HUVECs (Teng et al, 2015;Xie et al, 2017;Kang et al, 2020;Yu M. et al, 2020;Zhang et al, 2020) and enhanced expression of the angiogenesisrelated genes VEGF, ANG1, and ANG2 in hBMMSCs (Takeuchi et al, 2019) and the mRNA expression of PDGF, EGF, and ANG1 in HUVECs (Yu M. et al, 2020). In a rare study that directly compared EVs derived from the three most commonly employed clinical MSC sources, i.e., BMMSCs, ADMSCs and UCMSCs, ADMSC-derived EVs yielded the highest in vitro protein expression levels of VEGF, bFGF, and HGF in rat neonatal cardiomyocytes and also showed the strongest inhibitory effect on apoptosis (Xu H. et al, 2020).…”
Section: Comparing the Therapeutic Efficacy Of Bmmsc-derived And Admsmentioning
confidence: 96%
“…However, only few studies compared EVs from MSCs isolated from different sources. It has been recently reported that EVs from adipose tissue-derived MSCs (AD-MSCs) and from cardiac MSCs exhibit more potent angiogenic capacities than bone marrow-derived MSCs (BM-MSCs) (Chance et al, 2020;Kang et al, 2020). In addition, the capacity of EV production and secretory profile are higher in BM-MSCs than AD-MSCs, supporting a differential activity of EVs from different MSCs (Villatoro et al, 2019).…”
Section: Potential Therapeutic Use Of Mesenchymal Stem Cell-derived Ementioning
confidence: 99%